President Carter Policy Toward Arabian Gulf Carter Doctrine how it was drawn - Albedwawi, Saif Mohammed (Al-Adab Journal, 2022)
The aim of this study is to discuss United States of America foreign policy toward the Arabian Gulf during President Carter Administration. The emphasis of the paper is on mainly in the role of the National Security Adviser namely Zbigniew Brzezinski securing Carter Doctrine as a policy. After the Iranian revolution and the Soviets invasion of Afghanistan, US policy toward the Gulf region was rather passing through tremendous changes. To protect the American interests in the area, President Carter had to draw a new policy. In the end he came up with Carter Doctrine. This research is more interested in the decision-making during Carter’s era. Therefore, the process of this policy and how it came about would be discussed in detail. Furthermore, a background of those participants in drawing that policy as well as the struggle among them would be discussed too.